Love as a guide to morals. - Fitz-Gibbon, Andrew L., 1951- (Value Inquiry Book Series, 2012)
Love as a Guide to Morals is an entry-level introduction to the ethical importance of love. Written in conversational format this book looks uniquely at the complexity of love in human relationships and how love can guide ethical decision-making. The book suggests that love in all its intricacy-erotic/erosic love, friendship, affection, and agapic love-is the great good of human life. The book argues that love has a unifying power for morality, and is more suited to ethical thinking and practice than any other idea. Love as a Guide to Morals uses a modified Aristotelian argument (after Alsdair MacIntyre) and suggests "loving relationships" rather than happiness as the goal of human life.